2011
DOI: 10.1172/jci44907
|View full text |Cite
|
Sign up to set email alerts
|

Maternal T cells limit engraftment after in utero hematopoietic cell transplantation in mice

Abstract: Transplantation of allogeneic stem cells into the early gestational fetus, a treatment termed in utero hematopoietic cell transplantation (IUHCTx), could potentially overcome the limitations of bone marrow transplants, including graft rejection and the chronic immunosuppression required to prevent rejection. However, clinical use of IUHCTx has been hampered by poor engraftment, possibly due to a host immune response against the graft. Since the fetal immune system is relatively immature, we hypothesized that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 48 publications
(46 reference statements)
6
133
3
2
Order By: Relevance
“…In "villitis of unknown etiology," excessive infiltration of maternal CD8 + T cells into the villous tree of the placenta is associated with fetal growth restriction, pregnancy loss, and stillbirth (55). Furthermore, the potential impact on fetal physiology was recently illustrated by the demonstration that maternal T cells trafficking into the fetal circulation are the main barrier to engraftment following in utero hematopoietic cell transplantation (56). Our observations indicate that the study of adaptive T cell immune responses against fetal tissue should be an important area for future obstetric investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In "villitis of unknown etiology," excessive infiltration of maternal CD8 + T cells into the villous tree of the placenta is associated with fetal growth restriction, pregnancy loss, and stillbirth (55). Furthermore, the potential impact on fetal physiology was recently illustrated by the demonstration that maternal T cells trafficking into the fetal circulation are the main barrier to engraftment following in utero hematopoietic cell transplantation (56). Our observations indicate that the study of adaptive T cell immune responses against fetal tissue should be an important area for future obstetric investigation.…”
Section: Discussionmentioning
confidence: 99%
“…3 In mice, there is excellent engraftment of fully allogeneic HSCs in fetal recipients, 4,5 with donor-specific tolerance in chimeras. [6][7][8] In fact, it has been shown that the fetal immune response is not a barrier to engraftment as long as the maternal immune response is controlled. 7,8 Ideally, the introduction of a new antigen in the fetal environment should recapitulate multiple mechanisms of self-tolerance and lead to durable engraftment.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In fact, it has been shown that the fetal immune response is not a barrier to engraftment as long as the maternal immune response is controlled. 7,8 Ideally, the introduction of a new antigen in the fetal environment should recapitulate multiple mechanisms of self-tolerance and lead to durable engraftment. The mechanisms by which HSC transplantation leads to donor-specific tolerance have been studied extensively in the setting of postnatal BMT.…”
Section: Introductionmentioning
confidence: 99%
“…It should fetal circulation than in maternal that probably promote cell trafficking through placenta [15]. Nijagal et al shown that inflammatory disease (autoimmune processes, complication during pregnancy, congenital anomalies and others) [16] during pregnancy changes cell trafficking [17]. Similar to maternal cells, fetal cells were detected into different maternal organs and tissues: liver, kidney, bone marrow [18].…”
Section: Fluorescence In Situ Analysis (Fish)mentioning
confidence: 99%